Preliminary results of the excavations at Histria, the Acropolis Centre-South Sector (2013–2014) - Bottez, V.; Lițu, A.; Țârlea, A. (Materiale și Cercetări Arheologice, 2015)
This paper focuses on the results of excavations undertaken by the team of archaeologists of the University of Bucharest in the Acropolă Centru-Sud Sector at Histria (Constanţa County). The general stratigraphy so far consists of the vegetal layer, under which there are two layers of debris marking the initial moment of destruction and the moment of the final collapse after the abandon of the buildings affected by the fire. Underneath we identified the living surfaces of the last dwelling level, of which we have identified a large Late Roman building (CR01) S of street c. The latter has at least two construction phases, as well as two streets to its E and W (ST01 and ST02). ST02 also has two construction phases ; the first is perpendicular to street c, and was probably paved with large stone slabs, while the second is oblique to it and it is made up of a highly solidified layer of stones bound with earth, covered by a highly solidified layer of yellow clay (the same structure was identified in ST01)